2019
DOI: 10.3390/atmos10050257
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Parameters in the Generalized Extreme-Value Distribution Type 1 for Three Populations Using Harmonic Search

Abstract: Due to its geographical position, Mexico is exposed annually to cold fronts and tropical cyclones, registering extremely high values that are atypical in the series of maximum annual flows. Univariate mixed probability distribution functions have been developed based on the theory of extreme values, which require techniques to determine their parameters. Therefore, this paper explores a function that considers three populations to analyze maximum annual flows. According to the structure of the Generalized Extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Moretti and Mendes (2003) showed that small samples cause quality loss and less precision in parameter estimates using the method of maximum likelihood. Molina-Aguilar et al (2019) highlighted that multiple methods for estimating the parameters of the Gumbel distribution function are reported in the literature, with the moments and ML methods being the best known and most used of them all.…”
Section: Rbciambmentioning
confidence: 99%
See 1 more Smart Citation
“…Moretti and Mendes (2003) showed that small samples cause quality loss and less precision in parameter estimates using the method of maximum likelihood. Molina-Aguilar et al (2019) highlighted that multiple methods for estimating the parameters of the Gumbel distribution function are reported in the literature, with the moments and ML methods being the best known and most used of them all.…”
Section: Rbciambmentioning
confidence: 99%
“…Recently, many studies have focused on natural disaster risk analysis with probability distributions based on historical data, which are usually converted to frequencies. Regarding frequency analysis, particularly for extreme events, the objective is to define the events associated with a return period that provide information to carry out the design of hydraulic works, decreasing the uncertainty of the forecast (Molina-Aguilar et al, 2019). Costa et al (2018) commented that studies about the risks of extreme events enable the development of actions that minimize the effects of these events, thus strengthening the resilience of the affected communities, which generally have low technological development to overcome the damage triggered during disasters.…”
Section: Evaluation Of Generalized Extreme Value and Gumbel Distributions For Estimating Maximum Daily Rainfall Introductionmentioning
confidence: 99%
“…Optimization algorithms can be effective for optimizing the training of artificial intelligence models [30,31], multi-layer perceptron neural networks [32], and machine learning models [33]. The use of a meta-heuristic technique as a harmonic search was proposed [34]. In this way, new coefficients of Formula (3) are obtained for each hurricane analyzed.…”
Section: Validationmentioning
confidence: 99%
“…Thus, this study considered the three commonly used parameter estimation approaches: the maximum likelihood estimation, the probability weighted moments estimation, and the likelihood moment estimation approaches. It is essential to note that an alternative parameter estimation method, such as the maximum entropy and neural network approaches, have also been proposed by the previous studies [50][51][52][53]. The maximum entropy was used for estimating the parameters of several probability distributions such as gamma, Pearson type III, Log-Pearson type III, and generalized Pareto probability distributions [51,52].…”
Section: Introductionmentioning
confidence: 99%